Analisis Isi Buku At-Tafṣil Karya Muhammad Ridwan Salam Berdasarkan Teori William Frances Mackey - Nur Amalina; Hikmatul Lailaa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Teaching materials are a strategic component in the process of Arabic language learning, particularly in mastering the rules of nahwu (syntax) and sharaf (morphology). This study aims to analyze the content of the book At-Tafṣil fi Ma‘rifati Qawa‘id al-Lughah al-‘Arabiyyah by Muhammad Ridwan Salam based on William Frances Mackey’s theory, which encompasses four aspects: selection, gradation, presentation, and repetition. The book is an internal teaching material used exclusively at Markaz Darul Ilmi (MDI), an intensive Arabic language course institution in Wajo Regency, South Sulawesi, Indonesia. This study employed a qualitative approach using library research and content analysis techniques. The findings reveal that: (1) the selection aspect is fulfilled, as the materials are chosen in accordance with learning objectives, beginner students’ proficiency levels, and the one-month intensive learning program; (2) the gradation aspect is fulfilled, as the materials are organized from basic to more complex topics, progressing from morphology (sharaf) to syntax (nahwu); (3) the presentation aspect is fulfilled through the application of Mackey’s four presentation procedures, namely differential, ostensive, pictorial (tables and diagrams), and contextual procedures; and (4) the repetition aspect is strongly fulfilled in writing skills through essay-based exercises provided in each section, although it remains limited in speaking and listening skills. Therefore, At-Tafṣil generally meets the criteria of a language teaching textbook according to William Frances Mackey’s theory.